EFFECTIVENESS OF ADMINISTRATION OF RED GUAVA JUICE ONINCREASING HEMOGLOBIN LEVELS IN ADOLESCENT GIRLSWITH ANEMIA AT SMA NEGERI 1 PURWODADI - Sinta Amin Sholekah; Wahyu Utami Ekasari; Rosmala Kurnia Dewi (Jurnal Profesi Bidan Indonesia, 2024)
Background: : Anemia is a major health problem that occurs in society and is often encountered throughout the world, especially in developing countries like Indonesia. This disorder causes chronic disability which has a major impact on health, economic and social welfare conditions. Anemia often occurs in adolescent girls compared to adolescent boy.Objective: to determine the effectiveness of red guava juice in increasing hemoglobin levels in adolescent girls with anemia Method: This research uses a pre-experimental research design with a One Group Pretest Posttest design. Results: Based on the Wilcoxon test which aims to determine the effectiveness of giving red guava juice on increasing hemoglobin levels in adolescent girls with anemia at SMA Negeri 1 Purwodadi, a p value of 0.001 was obtained because the p value <0.05 means it is said that there is effectiveness of giving red guava juice on Increased hemoglobin levels in adolescent girls with anemia at SMA Negeri 1 Purwodadi with an average increase in Hb levels of 1.707gr/dl, this is   because guava juice contains vitamin C. Conclusion: giving red guava juice can increase 1.707 gr/dl hemoglobin levels in adolescent girls suffering from anemia